Tiếp cận hướng đối tượng cho hệ thống thông tin kho bạc nhà nước - Lợi, Phan Đinh; Hải, Nguyễn Thúc (Journal of Computer Science and Cybernetics, 2016)
The State Treasury of Vietnam (VNST) has been facing computerization need to carry out its heavy duty. In order to set up the information system for VNST, one approach of system analysis and design must be chosen. With its advantage features, Object-Oriented Approach is popularly used in the current information system community. The Object-Oriented Approach for the information system of VNST is introduced. For the whole system, this approach can reduce significantly the development cost and time, meanwhile keeping the reliant of the life-cycle. The object-oriented system analysis and design for the personnel subsystem has been described as an illustration of the technique in details.